Faktor yang Mempengaruhi Tingkat Kelelahan pada Perawat Rumah Sakit Pemerintah Provinsi DKI Jakarta - Winata, Susanty Dewi; Ingkiriwang, Elly; Sutanti, Yosephin Sri; Purnamawati, Purnamawati; Berliana, Adisa; Winaktu, Gracia JMT (Jurnal MedScientiae, 2024)
The issue of the quality of work of nurses in hospitals is something that needs attention, especially regarding the level of work fatigue by nurses. Work fatigue is a symptom related to work efficiency, skills and increased anxiety. Research shows that work fatigue has a significant impact on work accidents. This study aims to determine the factors that influence the level of fatigue in nurses in government hospitals. This research is a descriptive analytical research with a cross sectional approach. The population in this study were nurses at government hospitals. In this research, fatigue factors are divided into 3, namely age, gender and length of service. Sampling was carried out using the simple random sampling method. Data collection uses a questionnaire in the form of a Google form. Based on the results, it was found that there was a relationship between factors that influence fatigue and the level of fatigue, p - value <0.005 (0.000).